Can the Center Hold? - Kaplan, Rhona (Psychoanalytic Perspectives, 2021)
This paper describes and explores a racial conflict that occurred in a mixed race, sexual abuse survivors' group. Curiosity and productive dialogue surrounding race faces inherent difficulties and evokes powerful feelings that are often defended against through unconscious dissociative processes. This does not only lead to the denial of the traumatic impact of racism and racist acts, the denial in and of itself is traumatizing. I emphasize both the challenges and benefits that occurred in the processing of a group enactment around a racial conflict. The analysis of the group process is supported by psychoanalytic ideas surrounding the impact of racism and prejudice, contemporary relational theories of dissociation, the significance of witnessing and repair, and intersectional theory as it relates to race and gender. A discussion of the parallel processes between the group process and systemic racism in our society is interwoven as an important theme in the paper. This discussion demonstrates how the psychoanalytic process, whether group or individual, can be applied to our understanding of unconscious dynamics underlying the current divisiveness in our socio-political environment.